Inocybe carpinicola (Inocybaceae, Agaricales), a new nodulose-spored species from Hainan Province, China - He, Pan-Min; Fan, Yu-Guang; Deng, Lun-Sha; Yu, Wen-Jie (Phytotaxa, 2022)
In the present study, we describe a new nodulose-spored Inocybe species based on morphological and molecular phylogenetic evidences. The new species is discovered in a Carpinus forest in Hainan Province, tropical China. It is characterized by a small and slender habit, brown to umber brown pileus with an acutely pointed umbo, sub-distant lamellae, brownish stripes covered with appressed vesture, nodulose to sub-stellate basidiospores, and slightly thick-walled hymenial cystidia. Multi-locus phylogenetic analysis revealed its unique phylogenetic position and placed the new species in a well-supported clade comprising a series of nodulose- and spiny-spored taxa. A detailed description, color photos of different development stages of basidiomata and its micro-structures, and a discussion on its closely related taxa are provided.